Effects of Long-Term Tenofovir and Entecavir Treatment on Bone Mineral Density in Patients with Chronic Hepatitis B - Kahraman, Resul; Şahin, Abdurrahman; Öztürk, Oğuzhan; Çalhan, Turan; Sayar, Süleyman; Kanat, Evren; Doğanay, Levent; Özdil, Kamil (Turkish Journal of Gastroenterology, 2022)
Background: We aimed to investigate the long-term effects of tenofovir disoproxil fumarate and entecavir treatment on bone mineraldensity and evaluated the fracture risk assessment tool score in patients with chronic hepatitis B.Methods: A total of 58 chronic hepatitis B patients treated with tenofovir disoproxil fumarate (n = 40) and entecavir (n = 18) wereincluded in this prospective study from 2012 to 2016. To evaluate bone mineral density, dual-X-ray absorptiometry, fracture risk assessment tool, and laboratory examinations were performed in all patients first at baseline and second at the end of the study.Results: Age, sex, body mass index, fibrosis score, and viral load were similar in both groups. The mean follow-up was 33 months in thetenofovir disoproxil fumarate group and 31 months in the entecavir group. In patients treated with entecavir, there was no statisticallysignificant difference between baseline and second bone mineral density including lumbar spine (L) and total hip T score. In patientstreated with tenofovir disoproxil fumarate, there was a significant difference in the second bone mineral density compared with baseline bone mineral density for L3 (P = .033) and the major fracture risk assessment tool score (P = .03). When patients were divided into3 groups (normal bone mineral density, osteopenic, and osteoporotic), there was a significant increase in the number of osteopenicpatients in the total hip T score after tenofovir disoproxil fumarate treatment (P = .034).Conclusion: Our results suggest a decrease in the bone mineral density for lumbar spine (L3), an increase in the number of patients withhip osteopenia, and major fracture risk assessment tool score after long-term tenofovir disoproxil fumarate treatment in patients withrechronic hepatitis B.